IMPROVED ETHANOL PRODUCTION FROM SWEET SORGHUM THROUGH PRETREATMENT WITH ENZYMES FROM ITS ENDOPHYTES - ManPing Luo; KangXu Wang; MeiYuan Li; Dongwa Ma; Ziyu Liu; De-Min Li; XinGuo Zhang (Journal of Animal and Plant Sciences, 2024)
Sweet sorghum is an essential economic renewable energy crop for ethanol production through fermentation. The endophytes residing in plants decompose the plant cell walls using cellulase to access nutrients for their growth. Therefore, isolating the endophytes with high cellulase-producing capability from Sweet sorghum could be a potential approach for better hydrolysis of sweet sorghum, thereby increasing industrial ethanol production. In this study, forty-eight cellulase-producing endophytes were isolated from fresh sweet sorghum and screened by the Congo red staining method. Of them, strain X-25 with better hydrolysis activity was identified as Bacillus sp. through 16S rDNA sequencing. The alcohol production process was optimized by the orthogonal experiment, and the ethanol content reached a maximum of 10.84 g/100 mL. The Scanning electron microscopy (SEM) micrograph results demonstrated that cellulase in endophytic bacteria could effectively disrupt or diminish the cell wall structure of sweet sorghum straw. Overall, this study will provide a novel approach to production of ethanol from sweet sorghum straw.
Keywords: Sweet sorghum; Endophyte; Cellulase; Ethanol; Bacillus